The use of bituminous rocks and natural bitumens from a geonic point of view - M. A. Vysotskaya; A. V. Kurlykina; V. A. Tokarev (Вестник Дагестанского государственного технического университета: Технические науки, 2024)
Objective. The purpose of the work is to study the experience of using bituminous rocks from various deposits for the preparation of hot asphalt concrete or extracting bitumen from rocks from the point of view of geonics. Method. The following research methods are used: systematization, description and analysis. The necessary data is formed on the basis of information obtained from the analysis of domestic and foreign articles related to the topic of natural bitumen and practical experience in extracting bitumen from tar sand for the preparation of hot asphalt concrete mixture using bituminous rocks without the use of petroleum bitumen from various fields. Result. Various works on the preparation of hot asphalt concrete and bitumen from bituminous rocks are considered. The results obtained showed that the use of bituminous rocks for the preparation of hot asphalt concrete and bitumen based on them is possible, and the properties of the resulting material comply with current quality standards. Conclusion. The dependence of the properties and chemical composition of the material on the deposit in which it was mined has been established.